A rare case of synovial sarcoma with lung, heart and adrenal gland metastasis: a caution for patients and clinicians. Issue 8 (August 2021) - Jiang, Lisha; Ma, Qingxin; Zhu, Guonian; Lai, Xiaoqin; Liu, Qian; Shi, Ming; Ma, Hongsheng
A 68-year-old man presented to the Urology Clinic, West China Hospital, Chengdu, with a suspected right adrenal gland mass that had persisted for two months. He had no associated lumbodynia, dizziness or palpitation. Abdominal computed tomography (CT) revealed an uneven density and contrast-enhanced oval-like mass with smooth edges in the right adrenal gland. Laparoscopic right adrenal gland resection followed by histopathology confirmed a diagnosis of metastatic synovial sarcoma. The patient had a history of synovial sarcoma on the right upper leg 3 years previously that was surgically treated, but he had not undergone further treatment. Approximately 1.5 years later, he had undergone surgery for heart and lung metastasis from the synovial sarcoma of the thigh. At 5 months following laparoscopic right adrenal gland resection, abdominal CT showed a significant sign of right adrenal recurrence, and targeted therapy of 12 mg oral anlotinib, daily, was initiated. This relatively rare but alarming case highlights the importance of patient understanding and compliance to treatment.